2020
DOI: 10.1061/(asce)hy.1943-7900.0001631
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Head Accumulation due to Transient Wave Superposition in Pipelines

Abstract: Fluctuations in pressures are part of the normal behavior of water distribution systems. The common perception is that transient events dissipate quickly in a network without significant consequences; however, under certain circumstances, the superposition of waves from a transient event can magnify the pressure response, effectively accumulating head in a pipeline. This paper studies this accumulation phenomenon in a single pipeline from a theoretical point of view, with supporting numerical simulation and la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The so called “head accumulation”—already tested in Bohorquez et al. (2020) but in a single pipe (with a connection in series) for transients generated in the larger diameter pipe (low impedance)—happens also in a WDN for transients generated in the downstream end section of a service line.…”
Section: Effect Of the End‐user Discharge Changementioning
confidence: 96%
See 1 more Smart Citation
“…The so called “head accumulation”—already tested in Bohorquez et al. (2020) but in a single pipe (with a connection in series) for transients generated in the larger diameter pipe (low impedance)—happens also in a WDN for transients generated in the downstream end section of a service line.…”
Section: Effect Of the End‐user Discharge Changementioning
confidence: 96%
“…On the other hand, this remark cannot explain the different behavior of test series #2 and #3, since junctions 6 and 7 have the same shape. However, it is worthy pointing out the crucial role of the ratio between the main pipe cross‐sectional areas connected to the service line, and the service line itself, for a given pipe material: the smaller this ratio—that is, the higher the pipe impedance ratio—the larger the transmitted pressure wave (Bohorquez et al., 2020; Swaffield & Boldy, 1993). This is the reason why series #3 experiences the largest range of the no‐cavitating flow in the service line.…”
Section: Effect Of the End‐user Discharge Changementioning
confidence: 99%
“…partial closing of the valve. Recently, an approximate analytical method was derived [11] for the accumulated pressure head at the valve, during the first half pressure wave cycle. This method considers, only, frictionless elastic pipes consisting of two reaches with lower hydraulic impedance for the reach associated to the valve.…”
Section: A First Analytical Approachmentioning
confidence: 99%
“…for the Kelvin element i. Different terms of ( 10) are compensated as: the viscoelastic term is substituted from (11),…”
Section: B Attenuated Pressure Wave Headmentioning
confidence: 99%
“…A pumped piped network results in more wear and tear than a gravity-based system due to transitional pressures (Zaman et al 2021), and water hammer is the primary problem responsible for the deterioration (Bohorquez et al 2020). Numerous studies have reported the theory of water hammer and solution to minimize its impact on the network (Boulos et al 2005; Nault and Karney 2016; Wan and Zhang 2018).…”
Section: Introductionmentioning
confidence: 99%